Much Pain, Little Gain: The Consequences of the Iraq War for Iraqis and Americans - Jarevis, Dave (The Copernicus Journal of Political Studies, 2018)
The aim of this study is to provide details about contemporary reality in Iraq and the impact of the American invasion on Iraq and American interests in the ten years since 2003. The analysis of the various source material, including survey results, policy statements, and statistical data reveals that, while the invasion brought gains to both the Iraqis and the Americans, it did so at a great cost. The assessment of the outcome of that invasion is complicated by the fact that contemporary Iraq was influenced by two decades of the rule of Saddam Hussein, who dominated the government and repressed his real and imagined foes. In March 2003 the US hoped for a quick win; however, its troops were to remain in Iraq until December 2011, giving it significant influence throughout this period. While ten years have passed since the invasion, only ten years have passed and that may not be an adequate time frame in which to identify and evaluate gains and losses. Full text: http://bazhum.muzhp.pl/czasopismo/589/?idno=14763